Dysfunctional Immune System Reconstitution After Rituximab Exposure In Utero. Issue 4 (May 2021) - Clark, Rebecca; Lindsey, Diana; Whiteway, Susan; Mikita, Cecilia; Lieuw, Kenneth
Abstract : Rituximab is an antibody that binds to B-lymphocytes and is increasingly used during pregnancy. As an immunoglobulin G, it will transfer across the placenta. Previous case reports describe a diversity of clinical presentations in neonates born following rituximab exposure in utero. Our case is the first to offer the long-term experience in the care of an infant with severe neutropenia and prolonged profound hypogammaglobulinemia and class-switching B cell defect after in utero rituximab exposure.